Green Product: Its Impacts on Environmental Safety and Customer Satisfaction - Suryawardani, Bethani; Wulandari, Astri (International Journal of Engineering and Technology, 2019)
Green marketing has become a phenomenon to protect our earth from environmental destruction. As resulted, many companies from various industries have implemented the green revolution and fulfilled market demands by creating green products. The concern toward environment makes people change their behaviors toward the products they consume in their daily life. Hence, this paper explored the customer behavior towards green products, green customer satisfaction and the impact of green products on customer satisfaction and environmental safety. The data collection techniques used are observation, questionnaire and literature study. This study used Path Analysis for data analysis techniques with three tests, classical assumption test, regression analysis, and correlation analysis. The study result showed Green Product significantly affected Environmental Safety by 59.9% and to Customer Satisfaction by 39.4%. Meanwhile, Environmental Safety did not significantly affect the Customer Satisfaction, which was only 19.2%. The effects of Green Product on Customer Satisfaction through Environmental Friendly simultaneously were 28.2%, the remaining influenced by other factors which cannot be explained in this study.Â Â